2016
DOI: 10.1007/s00167-016-4301-0
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic-loaded bone cement reduces risk of infections in primary total knee arthroplasty? A systematic review

Abstract: III.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(22 citation statements)
references
References 26 publications
3
19
0
Order By: Relevance
“…In a more detailed look at these studies, there was one systematic review that analyzed over 6300 primary TKAs and THAs that showed no statistically significant differences in the rates of deep infection or superficial infection between the group that used AIBC and the group that used PBC[ 7 ]. Similar results were found in two other systematic reviews published in 2015 and 2016 as well[ 14 , 15 ]. However, these studies did not include the most up-to-date articles on primary and revision TKA procedures.…”
Section: Introductionsupporting
confidence: 91%
See 2 more Smart Citations
“…In a more detailed look at these studies, there was one systematic review that analyzed over 6300 primary TKAs and THAs that showed no statistically significant differences in the rates of deep infection or superficial infection between the group that used AIBC and the group that used PBC[ 7 ]. Similar results were found in two other systematic reviews published in 2015 and 2016 as well[ 14 , 15 ]. However, these studies did not include the most up-to-date articles on primary and revision TKA procedures.…”
Section: Introductionsupporting
confidence: 91%
“…Josefsson et al[ 28 ] proposed that the antibiotics from loaded cement do not reach the superficial parts of the wound in a sufficient concentration to prevent infection. This gave one explanation for the lack of statistical significance in superficial infection rates found throughout literature reviews as well[ 7 , 13 - 15 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite strong evidence of high local antibiotic concentrations, both immediately after implantation and sustainably over several months, [17][18][19] its clinical bene t remains controversial: while some meta-analyses report a signi cantly reduced PPI rate in primary and revision arthroplasty, [20,21] others found no effect. [22,23] This discrepancy is further aggravated by several key disadvantages, such as the development of antibiotic resistant bacterial strains, [24,25] thermal injury to surrounding tissues, [26,27] economical expenses for hospitals and tax payers, [28] and the risk of allergenic potential to surgeons and patients. [29][30][31] We recently reported on 250 patients who had been referred to our outpatient allergy clinic with a history of complicated cemented arthroplasty and suspected implant allergy.…”
Section: Introductionmentioning
confidence: 99%
“…Despite strong evidence of high local antibiotic concentrations, both immediately after implantation and sustainably over several months, [17][18][19] its clinical benefit remains controversial: while some meta-analyses report a significantly reduced PPI rate in primary and revision arthroplasty, [20,21] others found no effect. [22,23] This discrepancy is further aggravated by several key disadvantages, such as the development of antibiotic resistant bacterial strains, [24,25] thermal injury to surrounding tissues, [26,27] economical expenses for hospitals and tax payers, [28] and the risk of allergenic potential to surgeons and patients. [29][30][31] We recently reported on 250 patients who had been referred to our outpatient allergy clinic with a history of complicated cemented arthroplasty and suspected implant allergy.…”
mentioning
confidence: 99%